Gerakan Stop Asian Hate: Media, Politik dan Teknologi dalam Melawan Diskriminasi (Jurnal Nawala Politika, 2023)
This article explores the dynamic interplay between media, politics, and technology within thecontext of the Stop Asian Hate movement. Fueled by rising discrimination and violence againstAsian communities, this movement has harnessed the power of social media for awareness,challenged harmful media stereotypes, and driven legislative changes at various levels ofgovernment. It underscores the critical role of responsible media representation, politicaldiscourse, and technology-driven activism in the ongoing fight against discrimination and hate.While these elements have amplified the movement's impact, they also present challenges thatdemand collective efforts for a more inclusive society.